Effectiveness of injecting lower dose subcutaneous sterile water versus saline to relief labor back pain: Randomized controlled trial - Howieda Fouly (European Journal of Midwifery, 2018)
Introduction The aim of this study was to investigate the effect of a lower dose subcutaneous sterile water injection technique versus subcutaneous saline injection, on the relief of low-back pain for women during childbirth, and to explore the lasting effects of pain relief after administration (followed at 15, 30, 45, 90 and 120 minutes).